Animal Experimentation: The Statistics Speak for Themselves. Issue 6 (December 2016) - Balls, Michael; Combes, Robert D.
As a new consortium to promote animal experimentation is formed, the numbers of procedures reported to the UK Home Office continue to increase, and opportunities to replace them are not being taken